Forces of Nature : New Perspectives on Korean Environments - Park, Albert L.; Kim, Eleana Jean, 1971-; Fedman, David (Book collections on Project MUSE., 2023)
"Brings together scholars at the forefront of the emerging field of Korean environmental humanities to offer a multidisciplinary and transhistorical account of the Korean peninsula that centers the dynamic entanglements of human and nonhuman forces--flora, fauna, mineral deposits, and climatic conditions"--